The Efficacy of Using Cup Stacking Game in Teaching Speaking to Indonesian English as Foreign Language (EFL) Students - Yanpitherszon Liunokas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research aims at finding out the efficacy of using Cup Stacking Game in teaching speaking especially describing  to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of Cup Stacking Game effective in teaching conditional sentences to Indonesian EFL students?.  The research can be an addition to the persisting teaching speaking in English particularly the descriptive text through the use of Cup Stacking Game.  The research was conducted in August 2019. This research was conducted at First semester students of the English Study Program of Nusa Cendana University, Kupang.  The population of this research was First semester students of the English Study Program of Nusa Cendana University, Kupang in the 2020/2021 academic year. The number population is 160 in four classes.. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in mastering speaking and the post-test given to find out the students’ improvement in mastering speaking after giving the treatment by using Cup Stacking Game. The findings show that using Cup Stacking Game is effective in teaching speaking to Indonesian EFL students.  It is supported by the result of the significance test through SPSS 20 program that the P was 0.00.  Therefore, it is recommended to use the Cup Stacking Game in developing students’ speaking of Indonesian EFL students.